The Never-Ending Story of Complicated Hypertension - Weiss Emma; Sica Gabriel; Balahura Ana Maria; Japie Cristina; Bartos Daniela; Calmac Lucian; Minoiu Costin; Gulie Laurentiu; Badila Elisabeta (Sciendo, 2022)
Polyvascular disease affects up to 20% of atherosclerotic patients and portends a significantly higher cardiovascular risk, especially in terms of ischemic events. Therapeutic options mainly focus on aggressive pharmacotherapy and risk factor control. We present the case of a male obese patient with coronary artery disease, chronic renal disease, and refractory hypertension who underwent serial contrast imaging to document the extent and severity of his systemic atherosclerosis and was consequently referred for cardiovascular surgery to address total occlusion of the abdominal aorta. We further discuss specific features complicating the medical management of patients with severe hypertension, extensive atherosclerosis, and renal disease.